PENGARUH HARGA SAHAM, DIVIDEN DAN EARNING PER SHARE TERHADAP NILAI PERUSAHAAN DI BURSA EFEK INDONESIA - Riyanto, Riyanto; Efriyenti, Dian (Aksara Public, 2020)
Around the world, especially in Indonesia, competition and growth in the economy are increasing rapidly. In order to maintain business continuity or business continuity, economic actors will carry out various types of methods or strategies. Companies that have high company value will attract investors to plant shares so that company finance will also increase. The purpose of this study was to determine the effect of Stock price, Dividend and Earning per share on the value of the company on the Indonesia Stock Exchange. The population in this study were 9 pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. This study uses a sampling technique with a purposive sampling method so that there are 6 companies that meet the criteria.This study uses SPSS version 22 in processing data. F test results are stock price, dividend and earning per share simultaneously have a significant effect on firm value. T test results are partially, stock price and earning per share have a significant effect on firm value and dividend have no significant effect on firm value.